Standardised algorithm for peri- and postoperative wound management using fish skin grafts and octenidine in head-neck surgery - Fiedler, Lukas Sebastian; Lippert, Burkard M.; Klaus, Christoph; Plath, Michaela; Zweigart, Greta (International wound journal, 2025)
Complex reconstructions are often required after head and neck tumour resections, particularly in irradiated fields and areas with exposed bone. Fish skin grafts (FSG) have recently emerged as a potential adjunct in difficult wound healing. This case report series evaluates the effectiveness of FSG in combination with octenidine-based antiseptics, which have already shown beneficial results in split-thickness skin transplantation in high-risk patients, focusing on the time period for granulation and wound closure. Five patients with seven defects of different aetiology in the head and neck region received FSG applications. Defect sizes ranged from 2 × 4 cm (occipital) to 7 × 6 cm (temporal). Granulation was determined, with irradiated and non-irradiated wounds analysed separately. In three consecutive cases, octenilin gel (octenidine-based hydrogel) was implemented in the treatment regimen. Three patients achieved complete granulation, while two reached 66%-80% granulation. Non-irradiated wounds demonstrated faster granulation (mean 16.5 days) compared to irradiated wounds (mean 48.8 days). Although there was no statistical significance, a trend toward delayed healing in irradiated tissue was observed. Patients treated with octenilin gel showed favourable healing outcomes, including shorter granulation times. Despite the poor prognosis for uncomplicated healing in this cohort, both treatment protocols—octenisept with Flaminal forte and octenisept with octenilin gel—achieved satisfactory outcomes when combined with FSG transplantation. This approach appears promising for reconstruction in challenging head and neck wounds and warrants further evaluation in prospective clinical studies.
Zuerst veröffentlicht: 26. Oktober 2025
Illustrationen
Gesehen am 26.01.2026